Clinico-pathological study in large posterior fossa midline tumors - Sarkar, S; Hossain, MA; Mazumder, U; Rahman, KM; Akanda, NI (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jan;16(1):43-9.The abstract of this article is available on the PubMed website